How did nurses cope with the fast, comprehensive organisational changes at Danish hospital wards during the COVID-19 pandemic? An interview study based on nurses’ experiences - Hanne Irene Jensen; Bettina Ravnborg Thude; Mette Elkjær; Eva Hoffmann; Lilian Keene Boye; Kirsten Specht (BMJ Open)
Purpose The COVID-19 pandemic has influenced hospital work and healthcare workers all over the world. We explored how Danish nurses coped with the fast, comprehensive organisational changes in their workplace and identified barriers to and facilitators for organisations ensuring the best possible conditions for nurses to meet these challenges. The study focuses on the organisational setting and how it did or did not support the nurses in their work.Methods A qualitative explorative design was used in interviewing 23 nurses who had worked at a COVID-19 ward in one of three hospitals. Data were collected in the summer of 2020, and the analysis was inspired by Paul Ricoeur’s theory of narratives and interpretation.Results The presence of managers in the wards helped the nurses in the form of psychological and practical support. Working within an organisation that provides a safe environment was essential for nurses. The experience of a safe environment allowed nurses to ask questions, which supported them in finding solutions to specific tasks in the new and critical working environment. Barriers to handling the new situation were an absence of managers and a lack of a sense of belongingness and trust.Conclusion This study highlights the need for management to be present in the ward and for organisational support to be available to nurses so they can provide optimal treatment and care when working in new and unknown conditions during a pandemic. Practical assistance from managers to ease the job is beneficial. Furthermore, the presence of management is essential to provide psychological support and create a safe environment because this allows nurses to ask questions about how to better manage new and critical tasks.